Claudia Jones, the Longue Durée of McCarthyism, and the Threat of US Fascism. (1st July 2019) - Burden-Stelly, Charisse
Abstract : This article examines the ways that the Black Communist luminary Claudia Jones theorized the fascist threat in the United States in the early Cold War era. Drawing on her political thought and that of her comrades, the article begins by defining the peculiar brand of US fascism that loomed large in the minds of Black radicals who critiqued and militated against global capitalist exploitation. Then, "the longue durée of McCarthyism" is employed as an analytical framework to explicate the post-World War II "fascist-like" political formation that both preceded and exceeded Wisconsin Senator Joseph McCarthy's reign of repression. The next section highlights Jones's analysis of the 1940 Alien Registration Act, commonly known as the Smith Act, which was the first peacetime sedition act in US history. The focus of the final section is Jones's critique of, and subjection to, the Internal Security Act of 1950, also known as the McCarran Act, which President Harry S. Truman unsuccessfully vetoed. As Jones's biographers Buzz Johnson and Carole Boyce Davies note, taken together, the Smith Act and the McCarran Act created the conditions for the persecution of thousands of progressives, launched an all-out attack on their civil rights, and laid the foundation for immigration checks, deportation, and harassment particularly aimed at Black people. Ultimately, the lives of many Black anticapitalists, including Jones, Paul Robeson, C.L.R. James, and Ferdinand Smith were fundamentally disrupted by this "strong anti-Black and anti-communist hysteria" that portended the rise of fascism in the United States.